The Influence of Formal Sensory Aesthetics to Encourage Ecological Behavior: Case Study: Green Roof Central Market, Jakarta, Indonesia - Fiolita, Cindy; Sanjaya, Ridwan; Widjaja, Robert Rianto (International Journal of Environment, Architecture, and Societies, 2025)
This study aims to determine the influence of the sensory formal aesthetics of green roofs in encouraging ecological behavior. Jakarta's ecological crisis stems from lack of green spaces and unfriendly community behavior. Optimizing green roofs and appealing to aesthetics can stimulate environmental protection efforts. Qualitative approach with Robert K. Yin's case study method to propose a model proposition based on the influence of aesthetics on ecological behavior, testing it on mall visitors. Data collection through observation, surveys, semi-structured interviews, and expert validation. The research findings regarding the formal sensory aesthetics of the Central Market green roof can influence the ecological behavior of visitors as demonstrated in the model. Aesthetics with the goal of environmental education within it, influence behavior through the understanding of sustainability in its design and facilities. The relationship between aesthetics and ecological behavior includes experiences of returning to nature, feelings of connection with nature, and environmental knowledge media, which influence environmental awareness and ecological behavior. Visitor characteristics, duration, and frequency of visits also influence the ecological behaviors that occur and sensory perceptions of aesthetics. This study emphasizes the role of education in aesthetics to influence ecological behavior, through relationships in form of experiences, feelings and environmental knowledge.